2016
DOI: 10.1002/2016ja023397
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of magnetospheric electron density using the Cluster spacecraft

Abstract: Observations from the WHISPER (Waves of High frequency and Sounder for Probing of Electron density by Relaxation) instrument on board Cluster, for the interval spanning 2001–2012, are utilized to determine an empirical model describing the total electron density along closed geomagnetic field lines. The model, representing field lines in the region of 4.5≤L < 9.5, includes dependences on L and magnetic local time. Data verification tests ensured that the WHISPER data set provided unbiased measurements for low‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(81 citation statements)
references
References 63 publications
4
75
2
Order By: Relevance
“…The upcoming BepiColombo mission will provide direct measurements of plasma using the Mercury Plasma Particle Experiment (Saito et al, ) and the Search for Exospheric Refilling and Emitted Natural Abundances (Orsini et al, ) instruments aboard the magnetospheric and planetary orbiters, respectively. The magnetospheric orbiter of the BepiColombo mission will also provide data from the Plasma Wave Investigation (Kasaba et al, ) instrument, which could be used to infer electron densities from measurements of the plasma frequency, similar to the method used in Sandhu et al ().…”
Section: Discussionmentioning
confidence: 99%
“…The upcoming BepiColombo mission will provide direct measurements of plasma using the Mercury Plasma Particle Experiment (Saito et al, ) and the Search for Exospheric Refilling and Emitted Natural Abundances (Orsini et al, ) instruments aboard the magnetospheric and planetary orbiters, respectively. The magnetospheric orbiter of the BepiColombo mission will also provide data from the Plasma Wave Investigation (Kasaba et al, ) instrument, which could be used to infer electron densities from measurements of the plasma frequency, similar to the method used in Sandhu et al ().…”
Section: Discussionmentioning
confidence: 99%
“…The higher frequencies in the morning could be due to the asymmetric shape of the plasmasphere, which has been noted before (e.g., Chappell et al, ; Chi et al, ; Mathie et al, ; Poulter et al, ; Sandhu et al, ; Takahashi & McPherron, ; Warner & Orr, ). The plasma mass density is higher in the afternoon sector due to the refilling of flux tubes from the ionosphere throughout the day, as well as the average ion mass increasing (Sandhu et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…There is also an uncertainty in the value of p. Some authors have observed a peak in plasma mass density at the equator based on satellite measurements (e.g., Denton et al, 2004Denton et al, , 2006Denton et al, , 2009Takahashi & Denton, 2007;Takahashi et al, 2004). Sandhu et al (2016aSandhu et al ( , 2016b modeled this plasma distribution using electron density and average ion mass measurements from Cluster. Although Denton et al (2006) suggests that an equatorial bulge in mass density exists at L > 6, we will now investigate the impact such an equatorial bulge would have on our PEL-MUO data set.…”
Section: 1029/2018ja025487mentioning
confidence: 99%
“…They are instead consistent with the mass density estimates observed by Takahashi et al (). The causes of the significantly higher values obtained by Sandhu et al () might be (a) overestimation of the average ion mass for the cold plasma population ( <25 eV) which Sandhu et al (, , ) assumed to be equal to that obtained in the higher energy range (25 eV–40 keV); (b) contamination due to energetic radiation belt particles is not negligible also at L5.9 as was assumed by Sandhu et al (); (c) the mass density inferred from FLR measurements is not representative of the full plasma population but only of the low‐energy (cold) population.…”
Section: Modeling the Plasmatroughmentioning
confidence: 85%
“…Sandhu et al () developed a more sophisticated local time dependent empirical model of the plasma mass density based on measurements from WHISPER and CODIF experiments on board the Cluster satellites (Escoubet et al, ). They combined the electron number density model by Sandhu et al () with the average ion mass model by Sandhu et al () adding the dependence on the geomagnetic activity. The model can represent the plasma mass density distribution along magnetic field lines in the L‐range 5.9–9.5.…”
Section: Introductionmentioning
confidence: 99%